Analisis Hubungan Faktor Ekonomi dan Sosial dengan Kabahagiaan Dunia Berdasarkan Korelasi Kanonik - Julia Widiyanti; Cantika Dhiya; Ganesya Intantalia; Maulana Syah Putra Ramadhani; Elly Pusporani; Elly Ana (Journal of Mathematics Education and Science, 2026)
This study aims to analyze the multivariate relationship between socioeconomic factors and global happiness indicators. Data taken from the 2019 World Happiness Report, which covers 125 countries, was analyzed using canonical correlation methods. The socio-economic dimension is represented by four variables, namely social support, freedom to make life choices, log GDP per capita, and healthy life expectancy. Meanwhile, the second group of variables representing happiness indicators includes ladder score, positive affect, and negative affect. The first canonical function shows a very strong and statistically significant relationship between the two sets of variables. The resulting canonical correlation is very high, namely rho_1=0.9243 with a p-value < 0.001, and this function is able to explain 85.4% of the overlapping variance. The main contributing variables are social support with a loading of 0.983 and log GDP per capita of 0.914 in the socio-economic set, as well as ladder score with a loading of 0.997 in the happiness set. Meanwhile, the second and third canonical functions generated in this analysis show relatively limited contributions. The results of this analysis confirm that social support and economic prosperity play a fundamental role in a country's happiness. The policy implications of these findings emphasize the need for integrated interventions that simultaneously strengthen social capital and promote sustainable economic growth.